Different abnormalities of electroencephalographic (EEG) markers in quiet wakefulness are related to visual hallucinations in patients with Parkinson's and Lewy body diseases: Biomarkers (non‐neuroimaging): EEG and other biomarkers. (7th December 2020) - Babiloni, Claudio; Lopez, Susanna; Pascarelli, Maria Teresa; Lizio, Roberta; Noce, Giuseppe; Ferri, Raffaele; Soricelli, Andrea; Nobili, Flavio Mariano; Arnaldi, Dario; Famà, Francesco; Orzi, Francesco; Buttinelli, Carla; et al.
Abstract: Background: Parkinson's disease (PD) is the second‐most common neurodegenerative disorder that affects 2–3% of the population ≥ 65 years of age and may belong to cognitive deficits and dementia in 50% of cases. Disease with Lewy Bodies (DLB) is emerging as another important cause of dementia in pathological aging. PD and DLB are both due to intra‐neuronal Lewy bodies and are characterized not only by motor dysfunctions but also cognitive and/or psychiatric symptoms. An open issue is the extent to which these diseases are distinct entities. In this respect, here we compared cortical sources of resting state eyes‐closed electroencephalographic (rsEEG) rhythms in PD and DLB patients as a function of global cognitive status. Method: Clinical and rsEEG rhythms in demographic matched PD (N = 93), DLB (N = 46), Alzheimer's disease dementia (AD, N= 70) and healthy elderly (Nold, N = 60) subjects were available from an international archive. Pathological groups were matched as cognitive status. Individual alpha frequency peak was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were considered. The eLORETA freeware estimated rsEEG cortical sources. Result: Compared to the Nold subjects, the AD, DLB, and PD patients showed higher widespread delta source activities and lower posterior alpha source activities. Specifically, posterior alpha source activities were more abnormal in the AD than the DLB and PD groups, while widespread delta source activities were more abnormal in the PD and DLB than the AD group. As main novel results, in relation to the DLB and PD patients with low cognitive deficits and the control groups (Nold, AD), those with high cognitive deficits were characterized by higher parietoccipital delta source activities (DLB, Figure 1) and widespread alpha sources activities (PD, Figure 2). Conclusion: These novel results suggest that in DLB and PD patients resting in the quiet wakefulness, abnormalities in cortical neural synchronization at delta and alpha frequencies are differently related to cognitive status despite the essence of alpha‐synucleinopathy.